Recombinant BCG expressing the LTAK63 adjuvant improves a short-term chemotherapy schedule in the control of tuberculosis in mice - Trentini, Monalisa Martins; Kanno, Alex Issamu; Rodriguez, Dunia; Marques-Neto, Lazaro Moreira; Eto, Silas Fernandes; Chudzinki-Tavassi, Ana Marisa; Leite, Luciana Cezar de Cerqueira (Frontiers in Immunology, 2022)
Tuberculosis (TB) is one of the deadliest infectious diseases around the world. Prevention is based on the prophylactic use of BCG vaccine, effective in infants but as protection wanes with time, adults are less protected. Additionally, chemotherapy requires the use of many antibiotics for several months to be effective. Immunotherapeutic approaches can activate the immune system, intending to assist chemotherapy of TB patients, improving its effectiveness, and reducing treatment time. In this work, the recombinant BCG expressing LTAK63 (rBCG-LTAK63) was evaluated for its immunotherapeutic potential against TB. Bacillary load, immune response, and lung inflammation were evaluated in mice infected with Mycobacterium tuberculosis (Mtb) and treated either with BCG or rBCG-LTAK63 using different routes of administration. Mice infected with Mtb and treated intranasally or intravenously with rBCG-LTAK63 showed a reduced bacillary load and lung inflammatory area when compared to the group treated with BCG. In the spleen, rBCG-LTAK63 administered intravenously induced a higher inflammatory response of CD4+ T cells. On the other hand, in the lungs there was an increased presence of CD4+IL-10+ and regulatory T cells. When combined with a short-term chemotherapy regimen, rBCG-LTAK63 administered subcutaneously or intravenously decreases the Mtb bacillary load, increases the anti-inflammatory response, and reduces tissue inflammation. These findings highlight the potential of rBCG-LTAK63 in assisting chemotherapy against Mtb.